Rural Education Degree of the Universidade do Estado da Bahia (UNEB): art and reflections on the pedagogical work of graduates - Maria Jucilene Lima Ferreira; Lídia Barreto da Silva; Gilselia Macedo Cardoso Freitas (Universidade Federal do Norte do Tocantins, 2021)
The training of rural educators currently assumes the centrality of the debate on the theoretical-methodological foundations that provide educational processes with an emancipatory perspective. So, the article inquire about the place that art occupies in the teaching work of graduates of the degree in Rural Education, at the University of the State of Bahia (UNEB). The objective is to discuss conceptions and principles of the training of Educators, in the degree course in Rural Education and the contributions of art in this formative process, for the critical analysis of the place that art occupies in the teaching work of graduates. The methodology is anchored in dialectical historical materialism. The course recognition project, research data carried out in 2018 and the application of a questionnaire, by the Google forms digital platform, were used as reference. The results show that art is present in the pedagogical work of graduates, as well as assuming a prominent place. It concludes by pointing to artistic activities as a theoretical-methodological alternative for the training of rural educators and for the pedagogical work they carry out.